Eugregarine trophozoite detachment from the host epithelium via epimerite retraction: fiction or fact? - Valigurová, Andrea; Michalková, Veronika; Koudela, Bretislav (International journal for parasitology, 2009)
Eugregarines represent a diverse group of Apicomplexa parasitising numerous invertebrates. Their sporozoites generally develop into epicellular trophozoites attached to the host epithelium by a specialised attachment organelle known as an epimerite. They are considered peculiar protists due to their unique cell architecture and dimensions as well as their attachment strategy which is similar to that of cryptosporidia. Using electron and fluorescence microscopy, the fine structure of the epimerite with associated structures and the mechanism of trophozoite detachment from the host epithelium were studied in Gregarina polymorpha parasitising the intestine of Tenebrio molitor larvae. The epimerite appears to be a very dynamic structure whose shape dramatically changes depending on whether or not it is embedded into the host epithelium. The trophozoite's most fragile zone is the area below the membrane fusion site at the epimerite base. The epimerite plasma membrane forms basal radial ribs which are involved in increasing its surface and strengthening the epimerite-host cell junction. FITC-phalloidin labelling demonstrated the presence of filamentous actin in trophozoites along with its accumulation at the epimerite base and in the apical end of the protomerite, as well as a patch accumulation of filamentous actin in the protomerite of maturing and mature trophozoites. Indirect immunofluorescence revealed the presence of myosin in the cortical zone of the epimerite and in the membrane fusion site area. The data obtained strongly suggest that these structures could facilitate the detachment of a mature trophozoite from the host epithelium. Supported by data presented herein and our previous observations, we propose a new hypothesis on the mechanism of trophozoite detachment from the host epithelium based on epimerite retraction into the protomerite. This is contrary to the commonly accepted hypothesis describing gradual epimerite constriction and subsequent separation facilitated by contractility of the membrane fusion site (osmiophilic ring).
Keywords: buněčná membrána; Tenebrio; epitel; faloidin; Phalloidine; larva; aktiny; Apicomplexa; fluorescein-5-isothiokyanát; Host-Parasite Interactions; tkáňová distribuce; Microscopy, Electron, Scanning; fúze membrán; zvířata; Membrane Fusion; trofozoiti; fluorescenční barviva; organely; Fluorescent Dyes; Tissue Distribution; trávicí systém; mikroskopie elektronová rastrovací; Epithelium; Fluorescein-5-isothiocyanate; Actins; Larva; Animals; Cell Membrane; interakce hostitele a parazita; Organelles; Digestive System; Trophozoites